Automated impact device with non-synchronous impacts: a practical solution for modal testing during operation - Ong, Zhi Chao; Lim, Hong Cheet; Brandt, Anders (Zhejiang University Press, 2018)
Previous study has shown that synchronization of phases between impacts and the cyclic load component should be avoided to improve the effectiveness of operational modal testing, i.e. impact-synchronous modal analysis in obtaining a cleaner frequency response function (FRF) estimation with fewer number of averages. However, avoiding the phase synchronization effect is rarely achievable with the current manual impact hammer because of the lack of control of the impact timing. We investigate how to improve FRF estimation in the presence of harmonic disturbances, such as those present in operating rotating machines. An auto impact device is therefore introduced to replace the manual impact hammer. This device ensures that impact intervals can be applied at non-synchronous instances with respect to the harmonic disturbance. We demonstrate that this new device is a viable option for operational modal testing. It allows significant improvement in FRF estimation and shows good correlation of modal extraction data with benchmark experimental modal analysis results.